The Importance of a Holistic Approach During the Perioperative Period - (:unkn) unknown (My University, 2011)
Holism is the philospophy of understanding people by addressing factors that affect people in all situations. The goal of holistic nursing is to help patients integrate appropriate self-care into their lives. By providing holistic care, the perioperative nurse can help surgical patients experience fewer problems (eg, surgical trauma, pain, anesthetic complications), reach discharge more quickly, attain satisfaction with health care, and more easily resume normal activities. Holistic nursing may include the use of music, guided imagery, therapeutic massage, play therapy, touch therapy, and communication skills. Successful surgery for the patient means not only recovering but regaining physical, mental, and spiritual health as a whole. © 2011 AORN, Inc.
Keywords: Active listening; Alternative nursing care; Communication skills; Guided imagery; Holistic nursing; Music; Perioperative holistic nursing; Play therapy; Relaxation; Therapeutic massage; Touch therapy